From Diary to Pesantren: Integrating Islamic Religious Education as Socio-Psychological Capital for Golden Indonesia 2045 - Rafiqah Rahmah; Zainal Arifin; Sukiman Sukiman; Maragustam Siregar; Umniyah Al-Birtha (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2026)
Realizing Golden Indonesia 2045 requires superior human resources grounded in strong moral character. The family, as the primary socialization agent, plays a crucial role in integrating Islamic Religious Education (PAI) values. This study analyzes the integration of PAI values honesty, patience, sincerity, and responsibility in family parenting dynamics through an interdisciplinary lens of Developmental and Social Psychology. Using a qualitative case-study approach, data were collected through in-depth interviews with two purposively selected Muslim families in the Kebonarum District, Klaten, Central Java. The findings reveal that effective PAI integration relies not on verbal instruction or coercion, but on consistent non-verbal modeling and psychological internalization. Three key mechanisms were identified: (1) intrinsic motivation, a child's decision to enter pesantren was triggered by reading her mother's diary containing the aspiration; (2) modeling power, a father's calmness proved more effective than harsh discipline in shaping internal obedience; and (3) parenting inconsistency, where economic shifts disrupted consistency and hindered children's self-regulation. The study concludes that internalized Islamic religious education functions as socio-psychological capital, producing independent, responsible, and morally aware individuals, a fundamental prerequisite for Golden Indonesia 2045.